THE EFFECT OF TRANSPORTATION ON BLOOD GLYCOSE LEVELS AND ECTOPARASITE INVESTMENT IN PUNTEN CARP (Cyprinus carpio) - Wiwin Sumiati; Gunanti Mahasri; Sri Subekti (Universitas Airlangga, 2023)
Carp is one of the most popular sources of animal protein. Aquaculture products must be distributed through a transportation system to meet the demand for carp. Improper transportation techniques will cause the condition of the fish to deteriorate, thereby increasing stress, the parasites susceptible enter the fish's body. The aim of this study was to determine the effect of transportation on blood glucose levels and ectoparasite infestation in Punten carp. The method used in this study is an experimental method with descriptive approach by comparing the values of blood glucose levels and parasite infestations in fish before the transportation process and after the transportation process. The results of the analysis of water quality before the transportation and after the transportation process still within normal limits. In the transportation treatment, Mas Punten fish can increase blood glucose levels significantly with a value before transportation of 31.54 mg/dL and after transportation of 51.41 mg/dL. The increase in ectoparasite survival was not significant with an average number of 10.64 ind/head (medium) before transportation and 12.08 ind/head (moderate) after the transportation process. There is a correlation between blood glucose levels and ectoparasite infestation with the degree of correlation. Based on the chi test, it was found that the treatment of the Punten Mas fish transportation system can affect the blood glucose level of fish very significantly (sig> 0.01), but it is not associated with an increase in ectoparasite infestations that occur (.338>0.01).